(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Indian novelists in English have presenting woman as the centre of concern in their novels. A woman’s search for identity is a recurrent theme in their fiction. Kamala Markandaya is one of the finest and most distinguished Indian novelists in English of the post-colonial era who is internationally recognized. She has achieved a world-wide distinction by winning Asian prize for her literary achievement in 1974.